Subtalar Pronation Does Not Influence Impact Forces or Rate of Loading During a Single-Leg Landing - Hargrave, Melissa D. (National Athletic Trainers' Association, Inc., 2003)
OBJECTIVE: To identify the influence of static subtalar pronation (as measured by weight-bearing navicular drop [ND]) on ground impact forces and rate of loading during a single-leg landing. DESIGN AND SETTING: Subjects were grouped (n = 16 per group) on the basis of weight-bearing ND scores (supinators, <5 mm; neutral, 5–10 mm; pronators, >10 mm). Subjects performed 5 single-leg landings, dropping from a 0.3-m height onto a force platform. An electrogoniometer simultaneously recorded sagittal knee range of motion during the landing task. SUBJECTS: Forty-eight healthy volunteers participated. MEASUREMENTS: Peak vertical force was defined as the highest force recorded in the F(z) direction during landing. Rate of loading was defined as the peak vertical force divided by the time to reach the peak vertical force. Knee-flexion excursion was defined as the change in knee-flexion range from initial contact to peak vertical force. RESULTS: Peak vertical force (P = .769) and rate of loading (P = .703) did not differ among groups. Although secondary analyses identified significant negative correlations between peak force and rate of loading with knee excursion, the amount of knee excursion was similar among groups (P = .744). CONCLUSIONS: Our results de-emphasize the influence of static anatomical foot alignment on impact forces and absorption during a single-leg drop landing and provide further support for the role of knee flexion in dissipation of landing forces. Further investigations are needed to fully elucidate the role of subtalar pronation and other lower extremity alignment factors in force dissipation during dynamic functional activities.